Recognition: applications in aged care work - Austen, Siobhan; Jefferson, Therese; Ong, Rachel; Sharp, R.; Lewin, G.; Adams, V. (Oxford University Press, 2015)
Detailed arguments about the importance of recognition were present in Adam Smith’s Theory of Moral Sentiments but received little attention in classical and neoclassical economics. However recognition is re-emerging as an important concept in social and economic research. In this study we consider the importance of recognition and misrecognition for a nuanced understanding of the motivation to undertake paid care work. We use survey and interview data from a mixed-methods study of the employment intentions of Australian women working in aged care to investigate links between recognition, wage rates and intentions to remain working in the sector. Our findings suggest that low wages convey misrecognition and that both wages and misrecognition have adverse implications for the future labour supply of aged care workers. We conclude by considering particular challenges faced by the aged care sector and its workers in redressing low wage rates.